Proses Penyelesaian Sengketa Batas Tanah Antara Desa Pakan Dalam dan Desa Paramaian Tahun 2009-2021 - Rocgiyanti Rochgiyanti; Ahmad Parhani; Daud Yahya; Fathurrahman Fathurrahman (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
The village boundary dispute that occurred between Pakan Dalam Village and Paramaian Village in North Daha Subdistrict, Hulu Sungai Selatan Regency was triggered by the issuance of the Cultivation Rights Title of oil palm plantations that provided compensation to the affected areas. The purpose of this study is to determine the process of resolving land boundary disputes between Pakan Dalam Village and Paramaian Village in North Daha Subdistrict, Hulu Sungai Selatan Regency in 2009-2021.The method used in this research is the historical method. In the historical method there are four stages, namely heuristics, verification, interpretation, and historiography. Sources in the research were obtained through interviews with government, leaders, villagers, documents, books, and other related sources. The sources were verified, then data interpretation was carried out. After that, writing is done about the research studied and linking it to the theory used.The results showed that the dispute settlement started from the process of sending a letter from the Pakan Dalam Village Government to BPS HSS in 2009-2010 to the stage of asking for assistance to the HSS DPRD to be resolved fairly. In conclusion, the resolution of the village boundary dispute used a persuasive approach by the Daha Utara sub-district head. This method uses a settlement technique that is not adversarial and follows a conciliation approach to resolve the dispute.